(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
The process of incorporating water-soluble Eggshell Membrane (S-ESM) into Polycaprolactone (PCL) electrospun nanofiber webs was investigated, utilizing the hydrogen bonding interaction between S-ESM and catechin. PCL was first electrospun with catechin, and S-ESM was introduced into the resulting PCL/catechin nanofibers by immersing the fibers in S-ESM solution. Morphological observation suggested that S-ESM was incorporated with catechin and formed S-ESM/catechin nanoparticles, distributed in the PCL nanofiber webs. Analysis of FTIR spectra indicated that hydrogen bonding interactions were generated between PCL and catechin as well as between S-ESM and catechin. The bulk compression property of electrospun nanofiber webs was measured and the results showed S-ESM and catechin had effect on modifying the mechanical property of PCL nanofiber webs.